2020
DOI: 10.1093/geronb/gbaa225
|View full text |Cite
|
Sign up to set email alerts
|

Family Caregiving and Place of Death: Insights From Cross-national Analysis of the Harmonized End-of-Life Data

Abstract: Objectives Family is largely overlooked in research on factors associated with place of death among older adults. We determine if family caregiving at the end of life is associated with place of death in the United States and Europe. Method We use the Harmonized End of Life data sets developed by the Gateway to Global Aging Data for the Survey of Health, Ageing and Retirement in Europe (SHARE) and the Health and Retirement St… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 32 publications
2
10
0
Order By: Relevance
“…First, we focused on hospital out‐of‐pocket costs rather than all types of health care costs such as long‐term‐care and home‐care costs, as these costs may not be as amenable to change by having an AD due to their different goals of care related to each care venue. Additionally, Exit Interviews are not weighted for national representation as the HRS does not apply sample weight variables for decedents 26 . Depending on the timing of death, participants may have had low out‐of‐pocket costs if they died close to the last core interview, while others surviving the entire 2 years between interview windows could have had relatively higher costs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…First, we focused on hospital out‐of‐pocket costs rather than all types of health care costs such as long‐term‐care and home‐care costs, as these costs may not be as amenable to change by having an AD due to their different goals of care related to each care venue. Additionally, Exit Interviews are not weighted for national representation as the HRS does not apply sample weight variables for decedents 26 . Depending on the timing of death, participants may have had low out‐of‐pocket costs if they died close to the last core interview, while others surviving the entire 2 years between interview windows could have had relatively higher costs.…”
Section: Discussionmentioning
confidence: 99%
“…Participants are interviewed every 2 years following enrollment, and among those who die, HRS Exit Interviews are conducted with a proxy approximately 2 years following the participant's death. For this study, we used Harmonized HRS End‐of‐Life (1992−2014) data for 12,952 decedents' death‐related details, health conditions, health care utilization including hospital out‐of‐pocket costs, and AD completion status 24 . We only included participants from wave 6 through wave 12 Exit Interviews ( N = 9228) as earlier waves reported combined hospital and nursing home out‐of‐pocket costs, making it impossible to separate these costs.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Research has examined hospice staff perceptions of patient and family desire for control when referred to hospice ( Noh, 2019 ). Caregivers are an important determinant of the end-of-life experience, and their presence has been associated with an increased likelihood of dying at home ( Ailshire et al, 2021 ). Yet, how caregivers perceive the hospice admission has not previously been explored.…”
Section: Background and Objectivesmentioning
confidence: 99%
“…One nationally representative study from the United States, which set the presence of a spouse, household size, and number of daughters and sons as indicators of potential family care availability, found that larger household size and more daughters could increase the likelihood of dying at home ( Lei et al, 2021 ). A recent cross-national study affirmed that family caregiving was positively associated with home death in the United States and European countries ( Ailshire et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%